MARKET REACTION TO INTEREST RATE CUT ANNOUNCEMENTS: AN EVENT STUDY ON THE INDONESIA STOCK EXCHANGE - Meli Yuniar; Shahran Khairana Sofyan; Alex Pintu Batu; Okta Eka Putra (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to analyze the differences in the performance of all stock indices listed on the Indonesia Stock Exchange (IDX) before and after the implementation of a rate cut policy. A rate cut is a monetary policy instrument used to stimulate economic growth by increasing liquidity, lowering borrowing costs, and encouraging consumption and investment. Such policy changes may affect capital market movements; however, each stock index may respond differently depending on its characteristics and sectoral composition. This research employs a quantitative approach with a paired-sample comparative design. The population consists of all IDX stock indices, including IHSG, FTSE Indonesia, LQ45, Kompas 100, Bisnis-27, IDX30, IDX Islamic, IDX Main Board, IDX Syariah, IDX Sri-Kehati, IDX Banking, SMinfra18, MNC36, Investor33, Jakarta Islamic 70 (JII70), and IDX80. A saturated sampling technique was applied, with observation periods of 15 trading days before and 15 trading days after the rate cut announcement. Data were analyzed using normality tests (Shapiro–Wilk), followed by either the Paired Sample T-Test or the Wilcoxon Signed Rank Test depending on data distribution. The findings indicate that statistically there are no significant differences in the performance of most stock indices before and after the rate cut policy (p-value > 0.05). This suggests that the Indonesian capital market responds efficiently to monetary policy changes, and that the rate cut information may have been anticipated by investors. The results provide implications for investors, regulators, and policymakers in understanding market dynamics following monetary policy adjustments and serve as empirical evidence for investment decision-making and economic policy evaluation.